Using the new Scottish Longitudinal Outcomes database (LEO) to understand transitions from university to practice amongst nursing students - Alice Pearsons; Eleanor Mitchell; Euan Shields; Iain Atherton (International Journal of Population Data Science, 2025)
Objectives Nursing is facing substantial workforce challenges. Applications to study nursing have declined by 25% in Scotland, while 900 vacancies remain unfilled. The NHS Long Term Workforce Plan aims to grow the UK nursing workforce from 350,000 to 550,000 nurses by 2036/37. However, little is known about nursing students’ progression into practice.